Factores que inciden en la morosidad de la cooperativa de ahorro y crédito Kullky Wasi Ltda. Agencia Salcedo. - Toapanta Chicaiza, Patricia Janeth (2020)
The purpose of this research work is to identify the factors that affect default level of the loans granted to the members of the cooperative Kullki Wasi Ltda., Salcedo agency due to the fact that currently the financial institution registers a problem focused on late payment with 4.10%, being higher than the rest of the cooperatives of segment one, is a problem that directly affects the profitability of the same since if there is no adequate control it can cause a total closure of the entify, the type of methodology that was applied for the present study was by means of a quantitative approach, of descriptive type allowing to verify the dependent variable vs the independent variables. For the data collection, the survey instrument was used through the application of a structured instrument, the population were the members that accessed credits in the financial institution, the results obtained from the application of the surveys were analyzed through the application Chi-square statistics in the spss version 25 program, in which the main variables that affect late payment are obtained in this case are: the degree of education, family burdens, marital status and savings; the variables mentioned above are the more critical in the generation of credit defaults, the Cohen coefficient was used to measure the association of these variables, being marital status with 24,90% the one that most affected late payment.